스프레이 국화 형질전환을 위한 국내 육성 품종 선발 - 김경환(Kyung Hwan Kim); 서은정(Eun-Jung Suh); 한봉희(Bong Hee Han); 이연희(Yeon-Hee Lee); 이성곤(Seong-Kon Lee); 홍준기(Joon Ki Hong) (Weon'ye gwahag gi'sulji, 2015)
To select suitable spray chrysanthemum cultivars for Agrobacterium-mediated transformation, thirty-nine (39) spray cultivars bred in the National Institutes of Korea and a standard cultivar Jinba from Japan were collected and tested for regeneration rate and Agrobacterium infection assays. MS medium with $0.5mg{·}L^{-1}$ IAA and $1.0mg{·}L^{-1}$ BAP was used for shoot regeneration from leaf disks and internodes. The shoot regeneration rate in leaf disks was the highest in cultivar BRM, followed by cultivars VS, WW and YTM. The cultivar JB (Jinba) used as a transformation material in previous reports ranked similarly to cultivars PK and SPP. In shoot regeneration from internodes, the shoot regeneration rate was the highest for cultivar PA, followed by cultivar WW. The infection rate of leaves and internodes of 40 chrysanthemum cultivars with agrobacterium was investigated. Cultivars WPP, YNW, VS, PP, WW, FA, PA and YMN showed the highest infection levels in leaves, whereas cultivars WPP, PA, PK and YNW had the highest infection levels in internodes. Considering all of these results, cultivars VS and WW were the most appropriate for gene transformation of chrysanthemum using leaves, while cultivar PA was for internodes. 질전환에 적합한 국화 스프레이 타입 품종을 선발하기 위해서 국내 연구기관에서 육성된 39개 품종 및 일본품종인 스탠다드 타입 신마를 모아 재분화율과 아그로박테리움 감염도를 조사하였다. 잎과 마디 절편체로부터의 신초 재분화를 위하여 IAA $0.5mg{·}L^{-1}$와 BAP $1.0mg{·}L^{-1}$가 첨가된 MS 배지를 사용하였다. 잎 절편체로부터의 신초 재분화는 BRM 품종이 가장 높았고 VS, WW, YTM 품종순으로 분화되었다. 이전에 형질전환재료로 보고된 바 있는 신마는 PK, SPP 품종과 유사한 수준을 보였다. 마디 절편체로부터의 신초 재분화는 PA 품종에서 가장 높았으며 WW 품종이 다음으로 확인되었다. 40개의 국화 품종을 대상으로 아그로박테리움에 대한 감염도를 조사한 결과, 잎 절편체에서는 WPP, YNW, VS, PP, WW, FA, PA, YMN 품종이 가장 높았고 마디 절편체에서는 WPP, PA, PK, YNW 품종이 가장 높았다. 이상의 결과를 종합해 볼 때 국화의 잎 절편체를 이용한 형질전환은 VS와 WW 품종이 가장 적합한 반면에 마디형질전환에는 PA 품종이 가장 적합한 것으로 확인되었다.